Stride Pattern of the Lower Extremities Among Stride Types in Baseball Pitching - Chen, Shu-Wei; Tang, Wen-Tzu; Kung, Jung-Tang; Hung, Tsung-Ying; Chen, Yu-Lin; Lin, Wei-Hsuan; Burgee, Daniel J. (Frontiers in Sports and Active Living, 2021)
The present study investigated the differences in the stride pattern of the lower extremities among different stride types in baseball pitchers with the aim of evaluating stride movement and skills to improve training effectiveness. Thirty elite male college baseball pitchers volunteered to pitch on an indoor-mound-like force plate, where motion data of their fastest strike trials were collected using an eight-camera motion analysis system at a 200–250 Hz sampling rate. Pelvis center trajectories of each participant were calculated and further categorized into three groups: tall-and-fall (TF), dip-and-drive (DD), and mixed (MX) pitchers. Motion analysis revealed that DD pitchers initiated pivot–knee extension and pivot–hip adduction earlier than TF pitchers and accelerated their bodies sooner than TF pitchers. In addition, TF pitchers accelerated their bodies forward by pivoting their legs until the middle of the arm-cocking and acceleration phases. The movement patterns of MX pitchers were similar to those of DD pitchers in terms of pivot leg, although this occurred a little later in the stride. Our findings are useful in developing training strategies for coaches, players, and trainers to better meet the demands of different pitching styles.